A machine learning approach to credit default prediction and Individual credit scoring - Rahman, Md. Jaber; Ahmed, Hasib; Alam, A. N. M. Sajedul (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.